2006
DOI: 10.1111/j.1748-5827.2006.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of diabetes mellitus but not acromegaly in a cat with a pituitary macroadenoma treated with hypofractionated radiation

Abstract: The use of insulin-like growth factor 1 assays in the diagnosis and subsequent monitoring after radiotherapy of an acromegalic cat with a secretory pituitary adenoma and secondary insulin-resistant diabetes mellitus is described. Diabetes resolved, and exogenous insulin was no longer required for the maintenance of normoglycaemia 10 months after completion of a course of hypofractionated radiotherapy. However, insulin-like growth factor 1 remained elevated, and the cat's size and appetite continued to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 14 publications
1
36
1
Order By: Relevance
“…In the studies described in the past, types and techniques of radiation (Cobalt-60, betatron, linear accelerator), treatment planning (manual or computerized), as well treatment protocols (number of fractions, total radiation dose) varied considerably (Goossens et al, 1998;Peterson et al, 1990;Kaser-Hotz et al, 2002;Brearley et al, 2006;Littler et al, 2006;Mayer et al, 2006;Dunning et al, 2009;Sellon et al, 2009). In the studies described in the past, types and techniques of radiation (Cobalt-60, betatron, linear accelerator), treatment planning (manual or computerized), as well treatment protocols (number of fractions, total radiation dose) varied considerably (Goossens et al, 1998;Peterson et al, 1990;Kaser-Hotz et al, 2002;Brearley et al, 2006;Littler et al, 2006;Mayer et al, 2006;Dunning et al, 2009;Sellon et al, 2009).…”
Section: Catsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies described in the past, types and techniques of radiation (Cobalt-60, betatron, linear accelerator), treatment planning (manual or computerized), as well treatment protocols (number of fractions, total radiation dose) varied considerably (Goossens et al, 1998;Peterson et al, 1990;Kaser-Hotz et al, 2002;Brearley et al, 2006;Littler et al, 2006;Mayer et al, 2006;Dunning et al, 2009;Sellon et al, 2009). In the studies described in the past, types and techniques of radiation (Cobalt-60, betatron, linear accelerator), treatment planning (manual or computerized), as well treatment protocols (number of fractions, total radiation dose) varied considerably (Goossens et al, 1998;Peterson et al, 1990;Kaser-Hotz et al, 2002;Brearley et al, 2006;Littler et al, 2006;Mayer et al, 2006;Dunning et al, 2009;Sellon et al, 2009).…”
Section: Catsmentioning
confidence: 99%
“…In the studies described in the past, types and techniques of radiation (Cobalt-60, betatron, linear accelerator), treatment planning (manual or computerized), as well treatment protocols (number of fractions, total radiation dose) varied considerably (Goossens et al, 1998;Peterson et al, 1990;Kaser-Hotz et al, 2002;Brearley et al, 2006;Littler et al, 2006;Mayer et al, 2006;Dunning et al, 2009;Sellon et al, 2009). Interestingly, in several of those cases, diabetes was well controlled or even in remission (Littler et al, 2006;Dunning et al, 2009). Many of the treatments are not state-of-theart anymore and, therefore, results have to be interpreted with care.…”
Section: Catsmentioning
confidence: 99%
“…As in previous studies, no significant difference was found in IGF‐1 concentration pre‐ and post‐RT in HSDM cats . Ideally, more cats would have been recruited into this group.…”
Section: Discussionmentioning
confidence: 68%
“…This finding could indicate a lack of consistent efficacy of RT as a treatment for HS. Indeed, even in cases which see diabetes resolved after RT, ongoing soft tissue changes have been observed . Alternatively, RT may be associated with a late onset of treatment effect .…”
Section: Discussionmentioning
confidence: 99%
“…28,36 Bilateral adrenalectomy, radiotherapy and hypophysectomy have also been described as therapies for pituitary hyperadrenocorticism in cats. [29][30][31][37][38][39][40][41][42][43][44] Radiotherapy may temporarily resolve or control DM; however, acromegalic and hyperadrenocorticoid changes frequently persist. [40][41][42][43]45,46 Conclusions This is the second report of a cat with two discrete, morphologically distinct pituitary lesions consisting of a somatotrophic adenoma and a separate plurihormonal adenoma with positive immunohistochemistry for ACTH, FSH and MSH.…”
mentioning
confidence: 99%